The Challenges of Water Pollution: Enforcement of Water Pollution Control - Utama, I Made Arya; Suharta, I Nengah (Hasanuddin University, 2018)
Water demand continues to increase, while its availability was increasingly limited due to pollution. Therefore, the issue of legal sanction in the management of water resources was interesting to be examined because of the void of norm related to the sanction of administrative, civil and criminal sanction in Article 87-120 of Act Number 32 of 2009. So, this research was qualified into normative legal research with legal material from result of library research. The type of administrative legal sanctions were more effectively applied to protect water resources from pollution. Administrative Legal Sanction was not implemented through the judges, more easily and quickly implemented in providing protection against water resources, compared with sanctions of Criminal Law and Civil Law.